Faktor risiko perdarahan pasca persalinan primer - Ari Arfian Ningsih; Sujiyatini Sujiyatini; Asmar Yetti Zein (Poltekkes Kemenkes Yogyakarta, 2015)
Maternal mortality in of Yogyakarta in 2013 caused by bleeding ( 33%). Bleeding post delivery piece is themost primary of obstetrichaemorrhage as the cause ofmaternal death. Risk factors of bleeding post delivery primer i.e. age, parity, anemia, medical disease,induction of iabor. childbirth, episiotomy, duration and amniotic rupture early. There has been increasing bleeding scene in theaftermath of a primary in childbirth rsud wonosari. This research aims to get information about the risk of bleeding after a primary inchildbirth rsud wonosari year 2014. This research descriptive research by adopting both cross sectionai. The population in thisresearch is 47 mother who experienced postpartum hemorrhage after a primary in childbirth rsud wonosari 2014 as from 1 january2014 to 31 december 2014. An instrument used in this research is check list. Data analysis univariabel displayed in a frequencydistribution and the percentage of. Hasil penelitian faktorrisiko perdarahan pasca persalinan primer di RSUD Wonosari tahun 2014adalah paritas pada multipara (64%), dan metode persalinan pervaginam(87,2%). Bleeding after childbirth primary occurred on thenot with risk factors , which is aged 20-35 year (78.8 %) , not anemia (81%) , there is no medical disease (79%), not with induction(70,2%), the duration of normal delivery (38%), not episiotomi (85,1%) , and no amniotic broke early (85,1%) .